SECI driven creativity: the role of team trust and intrinsic motivation - Baldé, M.; Ferreira, A. I.; Maynard, T. (Journal of Knowledge Management, 2018)
Purpose The purpose of this paper is to examine employees' knowledge creation processes by leveraging a conceptual framework based on the socialisation, externalisation, combination and internalisation (SECI) model introduced by Nonaka and Takeuchi (1995). Given that many employees work within teams, in the current study, the authors examine the impact that team-level trust and intrinsic motivation have on an employee's SECI model and, in turn, the relationship between SECI model and individual creativity. As such, this work represents one of the first works to examine team-level factors that shape individual knowledge creation and creativity. Additionally, building on and extending previous SECI research, the authors develop a scale to measure SECI models that uses peer-rated assessments. Design/methodology/approach Data were collected from 431 employees who worked in 59 teams drawn from 51 companies in a variety of industry sectors, both SME's and corporate. To minimise common method bias, the SECI model questionnaire was adapted to the individual level through peer ratings instead of self-ratings (each employee rated three peers). To assess the hypotheses, hierarchical linear models using IBM SPSS were applied. The questionnaires were completed using both paper and online versions. Findings Results showed that SECI mediates the relationships between individual-level creativity and both team-level intrinsic motivation and trust. Furthermore, findings suggest that the scale developed is a reliable measure of SECI. Practical implications Knowledge creation and sharing practices should take into account both, a team's trust and its intrinsic motivation, which would result in creativity. Originality/value This paper examines the impact that team-level factors (i.e. team trust and team intrinsic motivation) have on individual SECI and creativity across a variety of industries. As such, this work is one of the first to examine the impact of team-level factors in shaping individual knowledge creation and creativity. Given the support that the study found for this hypothesis, this work demonstrates that team trust and intrinsic motivation are salient factors in shaping individual employee knowledge creation and creativity. Given the novelty of this work, the authors hope is that this study will be the foundation upon future cross-level studies of individual-level SECI and individual creativity can be built so as to improve SECI models.